1979
DOI: 10.3109/00498257909087261
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of azaheterocycles with mammalian liver aldehyde oxidase

Abstract: 1. Isoquinoline, cinnoline, quinoxaline, quinazoline and phthalazine were incubated with preparations of rabbit liver aldehyde oxidase. 2. The oxidation products, 1-hydroxyisoquinoline, 4-hydroxycinnoline, 2-hydroxy- and 2,3-dihydroxy-quinoxaline, 4-hydroxy- and 2,4-dihydroxy-quinazoline, and 1-hydroxyphthalazine were identified by comparison of their spectral and chromatographic characteristics with those of authentic compounds. 3. Michaelis-Menten constants are reported for the action of the parent heterocyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 27 publications
1
42
0
Order By: Relevance
“…phthalazine and purines), and aromatic or non-aromatic charged heterocycles with -CH=N + -(e.g. N I -methylnicotinamide and N-methylphthalazinium) [13][14][15]. AO also plays a major role in nitroreduction [16] and participates in the reduction of isoxazole and isothiazole ring systems [17].…”
mentioning
confidence: 99%
“…phthalazine and purines), and aromatic or non-aromatic charged heterocycles with -CH=N + -(e.g. N I -methylnicotinamide and N-methylphthalazinium) [13][14][15]. AO also plays a major role in nitroreduction [16] and participates in the reduction of isoxazole and isothiazole ring systems [17].…”
mentioning
confidence: 99%
“…Similarly excretion of HPZ would be expected to be greater in slow acetylators, and therefore chemical breakdown of this unstable metabolite would also give rise to more PZ in the slow acetylators. However PZ may also arise directly from hydralazine by oxidative metabolism (Streeter, unpublished results) and could also be produced from phthalazine by the action of aldehyde oxidase (Stubley, Stell & Mathieson, 1979). Any of these routes would be expected to yield more PZ in the slow acetylator phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Although AO has long been known to oxidize nitrogen-containing heterocycles (Knox, 1946;Stanulovi c and Chaykin, 1971;Stubley et al, 1979), its importance to drug metabolism first emerged in the case of carbazeran, a phosphodiesterase-2 inhibitor discontinued due to low oral bioavailability and short half-life in humans (Kaye et al, 1984(Kaye et al, , 1985. Based on analysis of chemical structure, a recent review suggested that a large number of drugs on the market (;13%) or candidate drugs (almost 45% of drugs in development) could be AO substrates (Pryde et al, 2010).…”
Section: Discussionmentioning
confidence: 99%